Reading the American novel 1920-2010 - Phelan, James, 1951- (Chichester, West Sussex, UK : Malden, MA : John Wiley & Sons Inc., 2013)
This astute guide to the literary achievements of American novelists in the twentieth century places their work in its historical context and offers detailed analyses of landmark novels based on a clearly laid out set of tools for analyzing narrative form. Includes a valuable overview of twentieth- and early twenty-first century American literary history Provides analyses of numerous core texts including The Great Gatsby, Invisible Man, The Sound and the Fury, The Crying of Lot 49 and FreedomRelates these individual novels to the broader artistic m
Introduction: Reading the American novel, 1920-2010 -- Principles of rhetorical reading -- The Age of Innocence (1920): bildung and the ethics of desire -- The Great Gatsby (1925): character narration, temporal order, and tragedy -- A Farewell to Arms (1929): bildung, tragedy, and the rhetoric of voice -- The Sound and the Fury (1929): portrait narrative as tragedy -- Their Eyes Were Watching God (1937): bildung and the rhetoric and politics of voice -- Invisible Man (1952): bildung, politics, and rhetorical design -- Lolita (1955): the ethics of the telling and the ethics of the told -- The Crying of Lot 49 (1966): mimetic protagonist, thematic-synthetic storyworld -- Beloved (1987): Sethe's choice and Morrison's ethical challenge -- Freedom (2010): realism after postmodernism.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: 1900-1999; American fiction -- 20th century -- History and criticism; Books and reading -- United States; LITERARY CRITICISM -- American -- General; American fiction; Books and reading; American fiction - 20th century - History and criticism; Books and reading - United States; United States; Electronic books; Criticism, interpretation, etc; Electronic books